Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2500/ajra.2013.27.3979
|View full text |Cite
|
Sign up to set email alerts
|

Increased Body Mass Index and Bronchial Impairment in Allergic Rhinitis

Abstract: The present study may suggest that BMI assessment should be routinely considered in AR patients for assessing risk for early bronchial impairment, such as suggesting possible evolution to asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
3
16
2
Order By: Relevance
“…Some studies showed that BMI is associated with the prevalence of allergic rhinitis. Our results are similar to the findings of these studies where people with allergic rhinitis have a higher BMI than those who did not suffer from allergic rhinitis [32] [33]. Overweight could have a role in the development of rhinitis [33].…”
Section: Discussionsupporting
confidence: 91%
“…Some studies showed that BMI is associated with the prevalence of allergic rhinitis. Our results are similar to the findings of these studies where people with allergic rhinitis have a higher BMI than those who did not suffer from allergic rhinitis [32] [33]. Overweight could have a role in the development of rhinitis [33].…”
Section: Discussionsupporting
confidence: 91%
“…10 Ciprandi et al 9 in their study of 100 patients with moderate to severe persistent AR found that BMI values were significantly lower in control subjects (mean 24.0) with respect to patients with rhinitis (mean 25.5). Another study by Ciprandi et al, 11 which included 155 patients with persistent AR alone and 155 healthy controls, established that BMI values were significantly higher in AR patients than in control subjects (p = 0.038). Differences in age range and the reliability of questionnaire-based diagnoses might be responsible for the reported controversial results on nasal allergies.…”
Section: Discussionmentioning
confidence: 99%
“…studies have reported positive associations between increased BMI and AR. [9][10][11] Nevertheless, the mechanism for the association between respiratory allergic diseases and obesity and the reasons for the apparent difference between men and women remain unclear. 2 Because both respiratory allergic diseases and obesity are characterized by inflammation, a common inflammatory pathway has been proposed as a plausible explanation for the association between respiratory allergy and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Forward steps with basic science, pathophysiology, 25 clinical trials, clinical guidelines, and evidence-based medicine 1,2,4,5,10,11,13,[14][15][16][17]20,21 and one step back with analysis of real-life outcomes (including analysis of failures) 3,6,7,9,12,13,18,19,23,24 will keep us progressing in the right direction, toward better patient care. Forward steps with basic science, pathophysiology, 25 clinical trials, clinical guidelines, and evidence-based medicine 1,2,4,5,10,11,13,[14][15][16][17]20,21 and one step back with analysis of real-life outcomes (including analysis of failures) 3,6,7,9,12,13,18,19,23,24 will keep us progressing in the right direction, toward better patient care.…”
Section: Progressmentioning
confidence: 99%